The global factor structure of exchange rates - Korsaye, Sofonias Alemu; Trojani, Fabio; Vedolin, Andrea (Journal of Financial Economics, 2023)
We propose a model-free methodology to estimate international stochastic discount factors (SDFs) that jointly price cross-sections of international stocks, bonds, and currencies in markets with frictions. We theoretically establish a SDF decomposition into one global factor and a currency basket. We show that our global factor prices a large cross-section of international asset returns , not just in- but also out-of-sample, across different currency denominations. Moreover, the pricing ability of the global factor is largely independent of the market structure or the size and type of market friction.